2020
DOI: 10.1002/jdd.12439
|View full text |Cite
|
Sign up to set email alerts
|

Virtual learning object: An asynchronous solution for virtual learning in dentistry post COVID‐19

Abstract: From its beginnings in the modern era, teaching, and learning in dentistry has been face-to-face, and it had as the object of evaluation and study the signs and symptoms F I G U R E 1 Complete process of construction of the virtual learning objects (VLO) of oral diseases, where specialists and students could see, feel, realize a good diagnosis, and finally develop a good treatment plan. This teaching process continues and has innovated didactic and methodological processes and procedures using virtual simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 5 publications
0
23
0
5
Order By: Relevance
“…The 16 included studies were published in three different types of journals: dental sciences, 13,14 multidisciplinary scientific publications, 15,16 , and educational publications 17–28 . The studies were conducted in nine different countries: Brazil, 15 Canada, 28 China, 16 Costa Rica, 13 France, 17 Nepal, 14 Peru, 18 Serbia, 24 and the United States 19–23,25–27 . Fifteen studies were published in English and one in Portuguese 15 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 16 included studies were published in three different types of journals: dental sciences, 13,14 multidisciplinary scientific publications, 15,16 , and educational publications 17–28 . The studies were conducted in nine different countries: Brazil, 15 Canada, 28 China, 16 Costa Rica, 13 France, 17 Nepal, 14 Peru, 18 Serbia, 24 and the United States 19–23,25–27 . Fifteen studies were published in English and one in Portuguese 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies 13,14,16–22,24–26 presented moderate methodological quality while three studies 15,23,28 showed high methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations